Bahasa Indonesia Bahasa Indonesia - Efli, Haura Tsamarah; Elida, Elida; Gusnita, Wiwik; Indrayeni, Wiwik (STKIP PGRI SITUBONDO, 2024)
This research is motivated by the high number of unemployed people, especially vocational school graduates, one alternative to overcome this condition is entrepreneurship. This research aims to describe student self-efficacy, describe entrepreneurial readiness and analyze the relationship between student self-efficacy and student entrepreneurial readiness. This type of research is quantitative with a correlational approach. The population of this study was 97 students in class XII Culinary at SMK Negeri 2 Bukittinggi in the 2024/2025 academic year. The sampling technique used is saturated sampling. Data collection was carried out by distributing questionnaires directly using a Likert scale which has been tested for validity and reliability. Data were analyzed using descriptive and correlation analysis. The results of the research show the overall self-efficacy of class. The results of the research show that there is a positive and significant relationship between Self-Efficacy and Entrepreneurship Readiness of class XII Culinary students at SMK Negeri 2 Bukittinggi.